Of Murines and Humans: Modeling Persistent Powassan Disease in C57BL/6 Mice - Stacey L. P. Scroggs; Danielle K. Offerdahl; Philip E. Stewart; Carl Shaia; Amanda J. Griffin; Marshall E. Bloom (mBio, 2023)
ABSTRACT Powassan infection is caused by two closely related, tick-transmitted viruses of the genus Flavivirus (family Flaviviridae): Powassan virus lineage I (POWV) and lineage II (known as deer tick virus [DTV]). Infection is typically asymptomatic or mild but can progress to neuroinvasive disease. Approximately 10% of neuroinvasive cases are fatal, and half of the survivors experience long-term neurological sequelae. Understanding how these viruses cause long-term symptoms as well as the possible role of viral persistence is important for developing therapies. We intraperitoneally inoculated 6-week-old C57BL/6 mice (50% female) with 103 focus-forming units (FFU) DTV and assayed for infectious virus, viral RNA, and inflammation during acute infection and 21, 56, and 84 days postinfection (dpi). Although most mice (86%) were viremic 3 dpi, only 21% of the mice were symptomatic and 83% recovered. Infectious virus was detected only in the brains of mice sampled during the acute infection. Viral RNA was detected in the brain until 84 dpi, but the magnitude decreased over time. Meningitis and encephalitis were visible in acute mice and from mice sampled at 21 dpi. Inflammation was observed until 56 dpi in the brain and 84 dpi in the spinal cord, albeit at low levels. These results suggest that the long-term neurological symptoms associated with Powassan disease are likely caused by lingering viral RNA and chronic inflammation in the central nervous system rather than by a persistent, active viral infection. The C57BL/6 model of persistent Powassan mimics illness in humans and can be used to study the mechanisms of chronic disease. IMPORTANCE Half of Powassan infection survivors experience long-term, mild to severe neurological symptoms. The progression from acute to chronic Powassan disease is not well understood, severely limiting treatment and prevention options. Infection of C57BL/6 mice with DTV mimics clinical disease in humans, and the mice exhibit CNS inflammation and viral RNA persistence until at least 86 dpi, while infectious virus is undetectable after 12 dpi. These findings suggest that the long-term neurological symptoms of chronic Powassan disease are in part due the persistence of viral RNA and the corresponding long-term inflammation of the brain and spinal cord. Our work demonstrates that C57BL/6 mice can be used to study the pathogenesis of chronic Powassan disease.